Institutionalization at Universities: Case Study of the Focal Institution and the Spawning Institutions - İnci Öztürk; Ali Balcı (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The purpose of this study is to analyze the institutionalization of (blinded) A University Faculty of Education as a focal institution, and (blinded) B University Faculty of Education and (blinded) C University Faculty of Education as spawning institutions where the faculty members serve. The common feature of these academics is that they graduated from any doctoral program of (blinded) A University in the past. In this context, views of faculty members on institutionalization of universities have been presented. “Case study” was employed in the research. The study group of this research is comprised of faculty members who have been working in focal institution (blinded) A University, and spawning institutions (blinded) B University and (blinded) C University in Turkey. According to research results, faculty members create hierarchies based on academic titles. Conflicts among faculty members in spawning faculties are resolved within the department by “arbitration.” The dominant organizational decision-making method employed by faculty members within their own faculties was “consensus.” Faculty members agree that graduates from their doctorate programs should be employed at the same faculty. The culture of the spawning faculties is similar to the culture of the teacher high school and the focal institution.